Hopf Galois Extensions and Non-commutative Rings (2019)
In this document we review the notion of Hopf Galois extensions, addressing remarkable examples, some properties and recent advances in such theory. Similarly, we present some families of non-commutative rings and algebras which arise in several applications and contexts. With particular examples, and using recent results on Hopf Galois theory, we study some interactions between such extensions and the mentioned families.